Implementasi Model Pendidikan Jasmani Berbasis Health-Promoting School dalam Meningkatkan Perilaku Hidup Sehat Siswa Sekolah - Muhammad Reza; Dedi Saputra; Novida Humaira (Arden Jaya Publisher, 2026)
This study aimed to examine the implementation of a Health-Promoting School-based Physical Education model in improving healthy lifestyle behaviors among elementary school students. A quantitative approach with a one-group pretest–posttest design was employed. The study was conducted at SD Negeri 18 Bireuen, Indonesia, involving 30 fifth-grade students selected through total sampling. The intervention was implemented over eight weeks by integrating physical activity, health education, and healthy lifestyle practices into physical education lessons. Data were collected using a validated and reliable healthy lifestyle behavior questionnaire. Descriptive statistics, the Shapiro–Wilk normality test, and a paired-samples t-test were used for data analysis at a significance level of 0.05. The results indicated that the mean healthy lifestyle behavior score increased from 65.00 ± 8.00 at pretest to 69.00 ± 7.80 at posttest. The paired-samples t-test revealed a statistically significant difference between pretest and posttest scores (t = 4.85, p < 0.001). Furthermore, the effect size (Cohen's d = 0.50) indicated a moderate effect of the intervention. These findings suggest that implementing a Health-Promoting School-based Physical Education model is effective in improving healthy lifestyle behaviors among elementary school students. Integrating health education into physical education learning may therefore serve as an effective strategy to promote healthy school environments and sustainable healthy behaviors